ANALISIS IMPLEMENTASI PROGRAM DETEKSI DINI KANKER SERVIKS MELALUI METODE INSPEKSI VISUAL ASAM ASETAT (IVA) DI PUSKESMAS KOTA SEMARANG - Meytri Saraswati; Ayun Sriatmi; Sutopo Patria Jati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Cervical cancer screening program by visual inspection with acetic acid (VIA) was breakthrough effort to accelearte the decrease of morbidity and mortality rate for cervical cancer. However, the implementation of this program in Semarang still has not optimum yet. The objective of this study was analyze the implementation of cervical cancer screening program by VIA at primary healthcare in Semarang. This research was descriptive-qualitative study. The data collection was done using indepth interview based on purposive sampling criteria of the primary healthcare center that had increase and decrease of extreme in VIA. The research subjects were 5 midwife executor of VIA as the main informant and for the triangulations informants were 1 head of infectious diseases unit in Semarang District Health Office, 5 head of primary healthcare center, and 5 women of reproductive age. Content analysis method was applied in the data analysis. The variables researched were implementation, communication, human resources, infrastructure, information, mind and character, motivation, division of works, and supervision. The result of the study show that implementation of program by VIA still had some constraint in promotion and education through media and socialization of program. The implementation was influenced by communication, human resources, materials, information, mind and character, motivation, division of works, and supervision. In communication , midwife and women of reproductive age still had not have good understanding of program information. Although infrastructures were fine but there was no avaibility of midwife and information. Mind, character, and motivation of midwife showed that need to be improved. Regular supervision and clear division of works need to between midwife and manager of infectious diseases unit.